Penerapan Pencatatan Keuangan Pada Pelaku Usaha Mikro Kecil Dan Menengah (UMKM) Bakso Tusuk Saipudin - Ni Made Anjani; Fera Wati; Nani Hartati (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Preparing financial reports is certainly an important factor for MSMEs. This research aims to: (1) understand the financial bookkeeping process, (2) analyze the application of Financial Recording in carrying out accounting bookkeeping, and (3) identify inhibiting factors or obstacles for Micro, Small and Medium Enterprises (MSMEs) of Bakso Tusuk Saipudin in the Clean Market Jababeka in implementing Financial Recording. This research is qualitative research. The research location was the Bakso Tusuk Saipudin UMKM in the Jababeka Clean Market in implementing Financial Recording. Data collection was carried out through interviews, documentation and observation. The data analysis technique is carried out through qualitative descriptive data analysis. The research results show that: (1) the management of Bakso Tusuk Saipudin MSMEs at the Jababeka Clean Market only prepares business activity reports which they consider to be financial reports. Even though the report is still very far from complying with financial accounting standards. In fact, MSMEs have tried to prepare reports that at least lead to conformity with accounting standards or accounting bookkeeping. (2) The correct accounting cycle has not been implemented by the management of Bakso Tusuk Saipudin UMKM at the Jababeka Clean Market, that is, it has not started with journalizing transactions, posting to the ledger, preparing a trial balance, adjustments, worksheet, until the issuance of financial reports. Complete financial report components in the form of financial position reports, profit and loss reports, changes in equity reports, cash flow reports and notes to financial reports have not been found in the reports prepared by MSME management. Thus, they have not prepared financial reports that are in accordance with financial records. (3) The obstacles and barriers encountered by the management of Bakso Tusuk Saipudin UMKM at the Jababeka Clean Market in preparing financial reports that are in accordance with financial records, are caused by several things, namely management's ignorance of the financial records required in preparing financial reports for the entity they manage or business. which they operate, financial management which is still handled by themselves.